Variation of phenotype in patients with glucocorticoid remediable aldosteronism. Issue 1 (January 1996) - Gates, L J; MacConnachie, A A; Lifton, R P; Haites, N E; Benjamin, N
Abstract : Glucocorticoid remediable aldosteronism (GRA), an autosomal dominant cause of primary aldosteronism, has been described as resulting in severe hypertension with premature death from stroke. We describe two new large pedigrees which include subjects who have the abnormal chimaeric gene strongly linked to GRA. The majority of affected members, who have only mild hypertension and normal biochemistry, are clinically indistinguishable from patients with essential hypertension. It is therefore likely that this condition is underdiagnosed.